Towarzyskość w butelce – wino w relacjach społecznych - Wyborski, Paweł (Człowiek i Społeczeństwo, 2012)
The purpose of this article based on in-depth interviews with Polish wine consumers/amateurs is to consider whether wine consumption may be perceived as an agent of social relations. I argue that collective wine drinking occasions may be sociologically understood as exemplifications both of Simmelian idea of sociability and Maffesoli’s modern tribalism. Consequently the main problem of the text is also to stress the role of social context in experiencing consumption pleasures as well as the significance of sharing common standards of taste in constructing and maintaining social relations.